Changes of Anterior Chamber Biometry and Relationship to Intraocular Pressure Changes after Phacoemulsification Emulsification Surgery in Non-Glaucomatous Eyes - Mohammed Qasim Al Nuwaini1 ; Giyathaldeen T. Neameh1 ; Farook M. Albusultan1 , Alyaa Abood Kareem2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Fifty percent of blindness worldwide is attributed to cataract, and cataract surgery is the most commonsurgery performed by ophthalmologist. Cataract surgery has its effects on the structures of the anteriorsegment, and hence the aqueous humor outflow, these may include more space in anterior chamber, widerangles, as the thick aging lens would be replaced by the thinner intraocular lens. So this study to investigatethe changes in anterior segment parameters and its correlation to IOP changes after phacoemulsification.A prospective Cohert study that was done at Ibn Al-Haitham Teaching Eye Hospital for patients plannedto have phacoemulsification, for 55 patients during 8 months, from the 1st of July/2018 until the 28th ofFebruary/2019. The data included full preoperative and postoperative assessment, key parameters were:axial length measurement, intraocular lens, anterior chamber depth, anterior chamber volume, anteriorchamber angle for the four quadrants and their mean value was calculated. It was done before the operationsand after two months from the operation. Findings were the mean age of the study group was 56.9years,with 30 (54.5%) males and 29 (52.7%) right eyes,. The mean axial length was 23.12±1.11 mm. There werestatistically significant differences in preoperative compared to postoperative values of IOP (decreased by4.55 mmHg), anterior chamber depth (increased by 0.74 mm), volume (increased by 32.75 µl), and meanangle (increased by11.78 degree) maximum inferiorly (12.31 degree) and minimum superiorly. There wereno statistically significant correlation between IOP changes with anterior chamber depth, volume, or angles,but there was a statistically significant correlation with preoperative IOP .Conclusions cataract surgerysignificantly decreases the IOP, and increase anterior chamber depth, volume, and angle. The decrease in IOPdoes not correlate with anterior chamber depth, volume, and angle. The decrease in IOP was significantlyhigher in patients with higher preoperative values of IOP.